Both sides of the sky [compact disc] - Hendrix, Jimi (Sony Music Commercial Music Group, 2018)
Jimi Hendrix's mastery of studio technology is put on display with the final installment in the trilogy of releases that opened up the archives. Ten of the thirteen tracks featured here have never been released.